Genotoxicity of anticancer drug Azathioprine (Imuran): role of Omega-3 (?-3) oil as protective agent - Elelaimy I.A, Elfiky S.A., Hassan A.M., Ibrahim H.M., Elsayad R.I. (Journal of Applied Pharmaceutical Science)
Omega-3 (ω-3), is long-chain, polyunsaturated fatty acids (PUFAs) of plant and marine origin. The present study was conducted to evaluate the protective effect of omega-3 against cytotoxicity and genotoxicity of anticancer drug; Azathioprine (Imuran): Male albino mice were administrated two levels; therapeutic (5mg|kg) and double therapeutic (10mg|kg) doses. Azathioprine was intraperitoneally injected for 3 times at 48 hour interval. Omega-3 was orally administered with 2 ml/kg for ten consecutive days either before or after Azathioprine treatments. At the end of experimentation period, samples of bone marrow were collected from five mice within each group for micronucleus assay. The liver and testis tissue samples were removed and stored at – 80 °C until use for DNA extraction, and determination of glutathione contents. Another animal group was treated at the same regimen and were used for the determination of sperm abnormalities and sacrificed after 35 days. The results indicated that oral administration of omega-3 either before or after treatment of Azathioprine was effective in reduction of the frequencies of Mn-PCEs, decreased the DNA fragmentation, total sperm abnormalities and significantly increased sperm count, percentage of PCEs, and enhanced the ratio of PCEs to NCEs. However, random amplified polymorphism of DNA (RAPD) showed distinct differences in animal groups intoxicated with Azathioprine before and after omega-3 treatment, which reflected DNA protective effect of omega-3. Depletion in glutathione content in testis was also observed in Azathioprine treated mice, which was improved by oral administration of Omega-3 either before or after treatment with Azathioprine.
Keywords: Omega-3, micronucleus test, sperm abnormalities, RAPD, Azathioprine Genotoxicity